Energy Efficiency Analysis by Game-Theoretic Approach in the Next Generation Network. Issue 4 (3rd July 2020) - Ghosh, Joydev
Abstract : This paper presents a game-theoretic scheme with anti-coordinated players by incorporating adaptation of femto base station (FBS) transmit power, attenuation of interference and utility function for open access mode and closed access mode, respectively. The deployment of femtocells in the networks is to produce improved energy efficiency (EE) and optimized response of payoff function. Additionally, the operating principle of the spectrum sharing scheme has been discussed in which FBS as a player acquire knowledge from utility responses of their strategic communications and revise their strategies at each level of the game process. Here, an FBS is regarded as a player in the game to select those users who are satisfied to a greatest extent and besides an FBS plays a role of mentor. Thereafter, the equilibrium concept has been invoked to aid the anti-coordinated players for the strategies. Finally, validated the simulation results are with its rarely studied extension in cognitive-femtocell networks.